Relapse of depression after rapid depletion of tryptophan. - Smith, K; Fairburn, C; Cowen, P (1997)
BACKGROUND: Major depression is a common disorder but the pathophysiology is poorly understood. Current hypotheses implicate deficient function of brain serotonin pathways because drugs that selectively increase brain serotonin activity are effective antidepressants. However, there is no direct evidence that lowered serotonin function causes major depression. We aimed to assess whether lowering of brain serotonin activity by depletion of its amino acid precursor, tryptophan, could provoke a short-term relapse of clinically significant symptoms in women vulnerable to major depressive disorder. METHODS: We studied 15 women who had suffered recurrent episodes of major depression but had recovered and were no longer on drug treatment. Patients received two amino acid mixtures in a double-blind crossover design. One of the mixtures was nutritionally balanced and contained tryptophan and the other was identical except it contained no tryptophan. Participants were scored on the Hamilton rating scale for depression (HAMD) before and 7 h after drinking each mixture. They also completed hourly self-rated measures of mood during this period. Blood samples were also taken at baseline and 7 h for measurement of plasma tryptophan. FINDINGS: The tryptophan-free mixture produced a 75% reduction in plasma tryptophan concentration. After drinking the tryptophan-free mixture, ten of the 15 women experienced temporary but clinically significant depressive symptoms. The mean difference in total HAMD scores (7 h minus baseline) were significantly higher after the tryptophan-free mixture than after the nutritionally balanced mixture (7.3 vs 0.15 [95% CI 4.5-9.9]; p < 0.001). No changes in mood were seen after taking the nutritionally balanced mixture. INTERPRETATION: We conclude that rapid lowering of brain serotonin function can precipitate clinical depressive symptoms in well, untreated individuals who are vulnerable to major depressive disorder. The findings support a key role for deficient serotonin function in the aetiology of depression.